Practical scientific and numerical computing with MATLAB and Python - Bashier, Eihab Bashier Mohammed (Boca Raton : CRC Press, 2020)
"This book concentrates on the practical aspects of numerical analysis and linear and non-linear programming. It discusses the methods for solving different types of mathematical problems using MATLAB and Python. Although the book focuses on the approximation problem rather than on error analysis of mathematical problems, it provides practical ways to calculate errors. The book is divided into three parts, covering topics in numerical linear algebra, methods of interpolation, numerical differentiation and integration, solutions of differential equations, linear and non-linear programming problems, and optimal control problems"--
OCLC-licensed vendor bibliographic record.
Keywords: MATLAB; Science -- Data processing; Python (Computer program language); COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Programming Languages / General; MATHEMATICS / Arithmetic